Antibacterial coating material, preparation method thereof and tracheal stent

By using antibacterial coating materials combined with polylactic acid, polycaprolactone and carbon nanoparticles on the tracheal stent, the problems of bacterial adhesion and drug release rate regulation are solved, and efficient biocompatibility and antibacterial effects are achieved. Personalized tracheal stent treatment.

CN119113234APending Publication Date: 2024-12-13QUZHOU PEOPLES HOSPITAL (QUZHOU CENT HOSPITAL)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411288010.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing tracheal stents are prone to bacterial adhesion and biofilm formation after implantation, resisting the immune system and antibiotic treatment, leading to inflammation and rejection, and the drug release rate is difficult to regulate and cannot provide personalized treatment.

Method used

Using polylactic acid, polycaprolactone and carbon nanoparticles as substrates, combined with antibacterial metal particles or antibiotic drugs, antibacterial coating materials are prepared through electrospinning technology, to regulate the release rate of antibacterial particles, and to improve the biological phase through shape memory effect Capacity and antibacterial utility.

Benefits of technology

It realizes excellent biocompatibility, degradability and antibacterial efficacy of antibacterial coating materials, can regulate the drug release rate according to different conditions, reduce the risk of postoperative infection and inflammatory response, and provide personalized treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113234A_ABST
    Figure CN119113234A_ABST
Patent Text Reader

Abstract

The invention discloses an antibacterial coating material which comprises a matrix and antibacterial particles, the antibacterial particles are distributed on the surface of the matrix, the matrix is made of polylactic acid, polycaprolactone and carbon nanoparticles, and the antibacterial particles are antibacterial metal particles or antibiotic drugs. According to the antibacterial coating material disclosed by the invention, simple materials such as the polylactic acid, the polycaprolactone, the carbon nano particles and the antibacterial particles are matched with one another, and the release speed of the antibacterial particles can be regulated and controlled through the shape memory effect of the polylactic acid and the polycaprolactone; and the antibacterial coating material can also be ensured to have excellent biocompatibility, degradability and antibacterial effect. The invention further discloses a tracheal stent and a preparation method of the antibacterial coating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer medical materials, and in particular to an antibacterial coating material, a tracheal stent and a method for preparing the antibacterial coating material. Background Art

[0002] The trachea is a vital part of the human respiratory system and plays an important role in transporting air. Trauma, infection, inflammation, benign tumors and other factors can damage the trachea, which can affect the patient's breathing, speaking and swallowing abilities, leading to a decrease in the patient's quality of life.

[0003] In the case of tracheal organ damage, the traditional treatment method is to use the patient's own tissue (autologous transplantation) or tissue from a donor (allogeneic transplantation). However, both methods have limitations. In the case of autologous transplantation, there is a lack of sufficient spare healthy tissue; for allogeneic transplantation, there is a problem of limited donors, and organ transplantation technology also requires immunosuppressive drugs, which has many limitations. Compared with traditional methods, the use of tracheal stent materials can control cell proliferation, differentiation, migration and adhesion, and appropriately promote the growth of extracellular matrix. However, one of the complications caused by stent implantation is that bacteria irreversibly adhere to the surface of the implant to form biofilms. These biofilms can resist the body's immune protection system and antibiotic treatment, leading to tissue rejection and inflammation between the stent and the tissue.

[0004] In order to reduce the problem of postoperative infection and reduce the impact of postoperative infection, the prior art usually only focuses on the improvement of the tracheal stent itself but not on the improvement of the coating of the tracheal stent. When improving the tracheal stent, it usually also focuses on its own material structure and preparation process. In addition, the materials required for the tracheal stent in the prior art are complex. For example, zinc-doped graphene phase carbon nitride-bismuth sulfide heterojunction composite powder is used, and the material cost is high. The prior art also does not pay attention to the regulation of the drug release rate on the tracheal stent, which is not conducive to providing personalized tracheal stent treatment methods for different patient conditions and is not conducive to improving the patient's recovery rate. Summary of the invention

[0005] The present invention provides an antibacterial coating material to solve the above problems.

[0006] In the first aspect, an embodiment of the present invention discloses an antibacterial coating material, which includes a substrate and antibacterial particles. The antibacterial particles are distributed on the surface of the substrate. The material of the substrate is polylactic acid, polycaprolactone and carbon nanoparticles, and the antibacterial particles are antibacterial metal particles or antibiotic drugs.

[0007] By adopting the above technical scheme, the antibacterial coating material of the present invention can achieve the regulation of the release rate of antibacterial particles through the mutual cooperation between simple materials such as polylactic acid, polycaprolactone, carbon nanoparticles and antibacterial particles, through the shape memory effect of polylactic acid and polycaprolactone, and can also ensure that the antibacterial coating material has excellent biocompatibility, degradability and antibacterial effect.

[0008] Optionally, based on mass, the carbon nanoparticles account for 1-25% of the antibacterial coating material, the antibacterial particles account for 1-15% of the antibacterial coating material, and the remainder is polylactic acid and polycaprolactone.

[0009] Optionally, the carbon nanoparticles are selected from at least one of the following: graphene oxide, reduced graphene oxide, graphene, graphene quantum dots, and carbon nanotubes.

[0010] Optionally, the antibacterial metal particles are selected from at least one of the following: silver, copper, gold, zinc oxide, and copper oxide.

[0011] Optionally, the antibiotic drugs are selected from at least one of the following: vancomycin hydrochloride, norvancomycin hydrochloride, polymyxin B, polymyxin E, levofloxacin, amoxicillin, and norfloxacin.

[0012] In a second aspect, an embodiment of the present invention further discloses a tracheal stent, the surface of which is coated with the antibacterial coating material described in any of the aforementioned embodiments.

[0013] By adopting the above technical scheme, the tracheal stent provided by the present invention can achieve regulation of the release rate of the antibacterial particles through the mutual cooperation of the polylactic acid, polycaprolactone and antibacterial particles of the surface antibacterial coating material, and through the shape memory effect of the polylactic acid and polycaprolactone, and can also ensure that the antibacterial coating material has excellent biocompatibility, degradability and antibacterial efficacy.

[0014] In a third aspect, an embodiment of the present invention further discloses a method for preparing an antibacterial coating material, which is used to prepare the antibacterial coating material described in any of the above embodiments, comprising:

[0015] Solution preparation: adding polylactic acid, polycaprolactone, carbon nanoparticles and antibacterial particles into an organic solvent, performing ultrasonic stirring to obtain a mixed solution;

[0016] Electrospinning: The apparatus used includes a selected container, a propulsion pump and an electrospinning apparatus, and the electrospinning apparatus includes a roller receiver; the mixed solution is placed in the selected container, and the selected container is placed in the propulsion pump, and the propulsion pump propels the mixed solution in the selected container toward the roller receiver; high voltage is applied to the selected container and the roller receiver to form a high voltage electric field, and the high voltage electric field is used to stretch the mixed solution to form a fiber film on the roller receiver;

[0017] Drying: The fiber membrane is dried to obtain an antibacterial coating material.

[0018] By adopting the above technical scheme, the method for preparing antibacterial coating materials can prepare antibacterial coating materials with excellent biocompatibility, degradability and antibacterial efficacy through electrospinning, and can also regulate the release rate of antibacterial particles through shape memory effect.

[0019] Optionally, the solution preparation step further includes: the mass ratio of polylactic acid to polycaprolactone is in the range of 0.1 to 16.

[0020] Optionally, the solution preparation step further comprises: the organic solvent is selected from at least one of the following: chloroform, dimethylformamide, dichloromethane, acetone, tetrahydrofuran.

[0021] Optionally, the selected container in the electrospinning step is a syringe with a needle on it, and the electrospinning step specifically includes the following steps: putting the mixed solution into the syringe, placing the syringe in a propulsion pump, and the distance between the propulsion pump and the roller receiver is in the range of 10 to 20 cm; the propulsion pump propels the mixed solution in the syringe toward the roller receiver at a speed in the range of 1 to 3 ml / h; connecting a high-voltage wire and a ground wire to the needle of the syringe and the roller receiver respectively to apply high voltage to the needle of the syringe and the roller receiver to form a high-voltage electric field, and the high voltage is in the range of 5 to 30 kV; installing tin foil on the roller receiver, and setting the rotation speed of the roller receiver in the range of 150 to 250 rpm, so that the roller receiver receives the fiber membrane; in the drying step, the fiber membrane is dried in the range of 24 to 48 hours and in the temperature range of 30 to 38°C to obtain an antibacterial coating material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram showing the macroscopic shape of the antibacterial coating material of Example 1 of the present invention;

[0023] Figure 2 A schematic diagram showing the microscopic morphology of the antibacterial coating material of Example 1 of the present invention;

[0024] Figure 3 A stress-strain curve diagram of the antibacterial coating material of Example 1 of the present invention is shown;

[0025] Figure 4 A degradation residual mass curve of the antibacterial coating material of Example 1 of the present invention is shown;

[0026] Figure 5 The in vitro drug release curve of the antibacterial coating material of Example 1 of the present invention is shown;

[0027] Figure 6The antibacterial zone diagram of the antibacterial coating material of Example 1 of the present invention against Staphylococcus aureus is shown;

[0028] Fig. 7A A graph showing the overall cell activity of the antibacterial coating material of Example 1 of the present invention on rat epithelial cells;

[0029] Figure 7B A schematic diagram showing living cells in the overall cell activity diagram of the antibacterial coating material of Example 1 of the present invention;

[0030] Figure 7C Schematic diagram showing dead cells in the overall cell activity diagram of the antibacterial coating material of Example 1 of the present invention

[0031] Figure 8 A curve diagram showing the relationship between drug release and time before and after shape memory of the antibacterial coating material in an embodiment of the present invention. DETAILED DESCRIPTION

[0032] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0033] It should be noted that in this specification, similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.

[0034] The terms “first”, “second”, etc. are only used for distinguishing descriptions and should not be understood as indicating or implying relative importance.

[0035] In the description of this embodiment, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this embodiment can be understood according to specific circumstances.

[0036] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0037] The inventor carefully studied the existing technology and found that the existing technology does not pay attention to the regulation of the drug release rate of the tracheal stent, nor the influence of the coating of the tracheal stent on the drug release, which is not conducive to providing more targeted tracheal stents for different conditions of different patients and is not conducive to further improving the patient's tracheal recovery speed. Based on this, the inventor thought that the antibacterial coating of the tracheal stent could be improved.

[0038] First, refer to Figure 1 The embodiment of the present invention discloses an antibacterial coating material, which includes a substrate and antibacterial particles. The antibacterial particles are distributed on the surface of the substrate. The material of the substrate is polylactic acid, polycaprolactone and carbon nanoparticles, and the antibacterial particles are antibacterial metal particles or antibiotic drugs.

[0039] The antibacterial coating material of the present invention is a coating applied on a tracheal stent, wherein the tracheal stent may be an existing tracheal stent. By adopting the above technical scheme, the antibacterial coating material of the present invention can achieve regulation of the release rate of the antibacterial particles through the mutual cooperation between polylactic acid, polycaprolactone, carbon nanoparticles and antibacterial particles, and through the shape memory effect of polylactic acid and polycaprolactone, and can also ensure that the antibacterial coating material has excellent biocompatibility, degradability and antibacterial effect.

[0040] The carbon nanoparticles account for 1-25% of the antibacterial coating material, the antibacterial particles account for 1-15% of the antibacterial coating material, and the remainder is polylactic acid and polycaprolactone.

[0041] Carbon nanoparticles account for 1 to 25% of the antibacterial coating material. Antibacterial particles account for 1 to 15% of the antibacterial coating material, which can play a good antibacterial role without causing damage to the patient due to excessive content.

[0042] Among them, carbon nanoparticles in the range of 1 to 25% (including the endpoint values ​​of 1% and 25%) can reduce the viscosity of the polymer (i.e., polylactic acid and polycaprolactone) and refine the diameter of the fiber (i.e., the fiber of the antibacterial coating material), and enhance the Young's modulus and tensile strength of the fiber (i.e., the fiber of the antibacterial coating material) by interacting with the polymer molecules (i.e., polylactic acid and polycaprolactone); can promote the penetration of water molecules in the fiber membrane of the antibacterial coating material, increase the swelling rate and water absorption rate of the fiber membrane, and accelerate the degradation of the fiber membrane; can also reduce the glass transition temperature of the fiber membrane, accelerate the thermal activation of shape memory, and improve the shape recovery speed and efficiency.

[0043] If the content of carbon nanoparticles is too little, it may result in the inability to effectively form a network structure or a continuous phase in the antibacterial coating material, thereby failing to fully improve the overall performance of the composite material of the antibacterial coating material. In addition, carbon nanoparticles can form strong interfacial interactions with polymer chains (in the present invention, polylactic acid and polycaprolactone) through hydrogen bonds, van der Waals forces, etc., thereby improving the interfacial bonding force of the composite material of the antibacterial coating material. When the content of carbon nanoparticles is too little, this interfacial interaction may not be sufficient to improve the interface performance.

[0044] If the content of carbon nanoparticles is too high, they may easily agglomerate on the fiber membrane of the antibacterial coating material to produce stress concentration, thereby reducing the mechanical properties of the fiber membrane of the antibacterial coating material; it will also increase the entanglement nodes of the fiber membrane of the antibacterial coating material, making it difficult for the grid structure of the fiber membrane of the antibacterial coating material to relax, resulting in a decrease in swelling rate, water absorption rate and memory deformation performance.

[0045] Preferably, the carbon nanoparticles account for 5-20% of the antibacterial coating material, which can better ensure that the carbon nanoparticles can reduce the viscosity of the polymer, increase the Young's modulus and tensile strength of the fiber, increase the swelling rate and water absorption rate of the fiber membrane, promote the degradation of the fiber membrane, and promote shape memory. More preferably, the carbon nanoparticles can account for 10-15% of the antibacterial coating material.

[0046] Different polymer materials have different biosafety and degradation products, and due to the different structures and molecular weights of polymers, there are great differences in mechanical properties and biocompatibility. In the present invention, the material of the matrix is ​​preferably polylactic acid and polycaprolactone. Polylactic acid and polycaprolactone are good bio-friendly polymer materials, and polylactic acid is approved by regulatory agencies of many countries including the U.S. Food and Drug Administration (FDA) for use in the human body. The decomposition products of polylactic acid and polycaprolactone are all products that are easily absorbed by the human body, such as H2O. Polylactic acid and polycaprolactone have excellent biocompatibility. Polylactic acid (PLA) and polycaprolactone (PCL) are both thermoplastic aliphatic polyesters, with excellent properties such as non-toxic, biodegradable, and biocompatible. At the same time, polylactic acid and polycaprolactone also have shape memory function, and the tracheal stent coating formed can change shape through thermal response, which is more convenient to implant in the patient's body and reduce the patient's pain. Furthermore, in the present invention, through the specific combination of polylactic acid, polycaprolactone, carbon nanoparticles and antibacterial particles, the shape memory effect of polylactic acid and polycaprolactone can be exerted, and the drug release rate can be regulated, which is beneficial to maximize the effect of the antibacterial coating material and is more conducive to the recovery of patients.

[0047] Reference below Figure 2 Combined with Figure 8The principle of the shape memory effect regulating the drug release rate is specifically explained. Since the shape memory stimulation causes partial relaxation of the grid structure in the fiber membrane of the antibacterial coating material, reducing the density of its cross-linking points, the free volume inside the membrane increases, and during the shape recovery process, the molecular chains need to be rearranged, the free space increases, and it is conducive to the entry of water molecules, so that the antibacterial particles (such as vancomycin hydrochloride) attached to the surface of the fiber membrane can be desorbed faster and released into the solution. Figure 8 The relationship between the drug release curve and time of the drug-loaded blend membrane before and after shape memory is shown. Among them, the VAN@GO fiber membrane is a fiber membrane formed by vancomycin hydrochloride, graphene oxide, polylactic acid and polycaprolactone. Figure 8 In the experiment, after the shape memory effect (SME) was produced, the fiber membrane released 21% of the vancomycin hydrochloride content in 2 hours, which was much higher than the release amount before the shape memory.

[0048] Further, in the matrix of the antibacterial coating material, the number average molecular weight of 110000g / mol≤polylactic acid≤300000g / mol, the number average molecular weight of 80000g / mol≤polycaprolactone≤200000g / mol. The use of polylactic acid and polycaprolactone with the above number average molecular weight is conducive to ensuring that polylactic acid and polycaprolactone can still maintain the excellent mechanical properties and biocompatibility of the entire antibacterial coating material after combining with carbon nanoparticles and antibacterial particles. In addition, low molecular weight polymers are difficult to electrostatically spin, and even if electrostatic spinning is used, the fiber diameter spun out is small and the mechanical properties are poor. The use of polylactic acid and polycaprolactone with the above number average molecular weight is also conducive to the subsequent preparation of antibacterial coating materials by electrostatic spinning, spinning out antibacterial coating materials with larger fiber diameters and excellent mechanical properties, which is conducive to avoiding the excessive viscosity of the material caused by the excessively high number average molecular weight, and can also avoid the negative impact of excessive viscosity on the formation of nanofibers by electrostatic spinning in the subsequent preparation process.

[0049] Furthermore, the carbon nanoparticles are selected from at least one of the following: graphene oxide, reduced graphene oxide, graphene, graphene quantum dots, and carbon nanotubes. As a reinforcement, carbon nanoparticles can effectively improve the mechanical properties, electrical properties, and thermal properties of polymer materials, while other inorganic nanoparticles do not have electrical and thermal conductivity. Other inorganic nanoparticles only improve the mechanical properties of polymer materials, but do not have multifunctional properties such as electrical and thermal conductivity.

[0050] In the present invention, carbon nanoparticles are used in combination with polylactic acid, polycaprolactone and antibacterial particles, which is beneficial to improving the overall mechanical properties, electrical properties and thermal properties of the antibacterial coating material.

[0051] Among them, in terms of mechanical properties, the improvement of mechanical properties can enable the antibacterial coating material on the tracheal stent to resist the effects of swallowing and other stretching and compression in the human body on the antibacterial coating material, thereby preventing the antibacterial coating material from being damaged or falling off the stent.

[0052] In terms of electrical properties, the electrical properties of the antibacterial coating material may affect the voltage of the high-voltage electric field applied in the electrostatic spinning method in the subsequent material preparation process. By improving the electrical properties of the antibacterial coating material, the voltage of the applied high-voltage electric field can be reduced (the reason is that after the carbon nanoparticles are combined with polylactic acid and polycaprolactone, the viscosity of polylactic acid and polycaprolactone can be reduced, and the magnitude of the applied voltage is related to the change in viscosity. After the viscosity decreases, the corresponding applied voltage will also decrease). Exemplarily, when the carbon nanoparticles are not added, the voltage of the high-voltage electric field that needs to be applied during the electrostatic spinning preparation material is 16-18kV, then the voltage of the high-voltage electric field that needs to be applied after the carbon nanoparticles are added may be reduced to 11-13kV, which helps to save energy, and reducing the voltage can also improve safety. Further, the carbon nanoparticles have electrical conductivity. By combining carbon nanoparticles, polylactic acid, polycaprolactone and antibacterial particles, the antibacterial coating material obtained can also apply microcurrent to the human body during the use of the human body, perform electrical stimulation, and promote cell proliferation and growth.

[0053] In terms of thermal performance (i.e. thermal conductivity), thermal conductivity mainly affects the shape memory of the antibacterial coating material, which can reduce the glass transition temperature of the fiber membrane of the antibacterial coating material, accelerate the thermal activation of shape memory, and improve the shape recovery speed and efficiency. By improving the thermal performance of the antibacterial coating material, the grid structure of the fiber membrane can be relaxed, and the drugs (i.e. antibacterial particles) in the antibacterial coating material can contact the aqueous solution faster, detach from the fiber, increase the drug release, and thus prevent bacterial infection faster.

[0054] In addition, in the present invention, when the antibacterial particles are antibacterial metal particles, the carbon nanoparticles can be combined with the antibacterial metal particles through hydrogen bonds and interaction forces such as van der Waals forces, and have a stable structure. The carbon nanoparticles are combined with the nanofibers in an embedded and interactive manner, and the antibacterial metal particles are not easy to separate from the antibacterial coating material, thereby preventing the deposition of heavy metal particles and avoiding the negative impact of heavy metal particle deposition on human health.

[0055] The particle size of the carbon nanoparticles is in the range of 100 to 2000 nm. When the particle size of the carbon nanoparticles is within this range, it is advantageous for the carbon nanoparticles to be more easily doped into the polymer nanofibers of the antibacterial coating material. Preferably, in this embodiment, the particle size of the carbon nanoparticles is 1070 nm. With this particle size, the carbon nanoparticles have better dispersibility, and can more effectively enhance the mechanical properties of the fibers of the antibacterial coating material. The fibers of the antibacterial coating material are more easily evenly dispersed without agglomeration (agglomeration will lead to stress concentration and easy fracture), making the antibacterial coating material easier to process.

[0056] In the present embodiment, preferably, carbon nanoparticles are graphene oxide. Graphene oxide is rich in oxygen-containing functional groups on its surface and edge relative to other inorganic nanoparticles, such as carboxyl, hydroxyl and epoxy groups, and the introduction of these functional groups has hydrophilic characteristics compared to other inorganic nanoparticles, so that graphene oxide can show good dispersibility in a variety of solvents including water. In addition, graphene oxide can form a close combination with other substances through covalent bonds (based on the electrostatic interaction between atoms) and non-covalent bonds (such as π-π conjugated action, ionic bonds and hydrogen bonds). More specifically, graphene oxide, as a carbon nanofiller, has a high specific surface area, and this two-dimensional structure allows graphene oxide to disperse in these polymer matrices of polylactic acid and polycaprolactone, and can form a large amount of interfacial interactions with polymer molecules, thereby effectively transmitting and dispersing stress, while the oxygen-containing groups on the graphene oxide surface can interact with the molecules in the polymer matrix through non-covalent bonds such as hydrogen bonds, van der Waals forces, so that graphene oxide is closely combined with polymers, and the mechanical properties of the reinforcing material are enhanced.

[0057] In the above embodiments, the antibacterial particles can be antibacterial metal particles or antibiotic drugs, either of which can be selected. Antibiotic drugs can be drugs commonly used in modern medicine to treat bacterial infections in patients. Antibacterial metal particles can also play a role in treating bacterial infections. The antibacterial metal particles have a wide antibacterial spectrum and can effectively inhibit a variety of fungi, which is more conducive to dealing with bacterial resistance. In addition, the preparation process of antibacterial metal particles and antibiotic drugs is simple, the time cycle is not too long, the materials are simple, the cost is low, and they can also have good antibacterial effects.

[0058] It should be noted that in antibacterial particles, antibacterial metal particles and antibiotics cannot be used at the same time. Although in theory both antibacterial metal particles and antibiotics have antibacterial properties and can treat bacterial infections, superposition should achieve better antibacterial effects. However, in actual use, antibacterial metal particles may be easily wrapped by antibiotics, so that the antibacterial metal particles cannot come into contact with bacteria and lose their antibacterial function. In addition, the superposition of antibacterial metal particles and antibiotics may also cause cell damage.

[0059] When the antibacterial particles are antibacterial metal particles, the particle size of the antibacterial metal particles is in the range of 50 to 150 μm. When the particle size of the antibacterial metal particles is within this range, the size of the antibacterial metal particles is very small and can penetrate the cell wall of the bacteria and enter the interior of the cell, destroying the metabolic process inside the cell, thereby killing the bacteria. Preferably, in this embodiment, the particle size of the antibacterial metal particles is 81 μm. With this particle size, while ensuring the bactericidal effect, the antibacterial metal particles can be better combined with the carbon nanoparticles and will not separate from the carbon nanoparticles, thereby avoiding interference with the normal function of the immune system and avoiding inflammation and immune response as much as possible.

[0060] Furthermore, the antibacterial metal particles are selected from at least one of the following: silver, copper, gold, zinc oxide, and copper oxide. Preferably, the antibacterial metal particles are silver nanoparticles. Silver nanoparticles can be tightly adsorbed on the cell wall and cell membrane of bacteria, and then penetrate into the interior of the cell, causing damage to organelles and biomolecules. When silver nanoparticles are combined with carbon nanoparticles (such as graphene oxide), they can not only play an antibacterial role, but also smaller silver nanoparticles may be more likely to interact with cell membranes due to their higher specific surface area, provide adhesion points for cells, and promote cell proliferation.

[0061] Furthermore, when the antibacterial particles are antibiotics, the mass percentage of the antibiotics is 1-15%, and the purity of the antibiotics is 99.95%. Too little antibiotics cannot kill bacteria in the trachea, and too much antibiotics will affect the activity of cells such as tracheal epithelial cells, causing damage to the human body. By controlling the content of antibiotics in the antibacterial coating material, it can be ensured that the obtained antibacterial coating material has excellent antibacterial efficacy. The purity of antibiotics is 99.95% to achieve a good antibacterial effect. If the purity is further improved, a more complex preparation process is required, and the cost increases.

[0062] Antibiotics can be selected from at least one of the following: vancomycin hydrochloride, norvancomycin hydrochloride, polymyxin B, polymyxin E, levofloxacin, amoxicillin, norfloxacin. In terms of tracheal infection, it is mainly caused by the influence of Gram bacteria, including those strains that are resistant to other antibiotics (such as methicillin). Preferably, in the present embodiment, the antibiotic is vancomycin hydrochloride. Compared with other antibiotics, vancomycin hydrochloride shows extremely high efficacy against Gram-positive bacteria, so vancomycin hydrochloride is an important choice for treating serious infections such as methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus epidermidis and enterococci. However, although vancomycin hydrochloride is very effective in treating these refractory infections, its use is also accompanied by some significant side effects. Long-term or high-dose use of vancomycin hydrochloride may lead to a series of adverse reactions, including adverse reactions such as vomiting, ototoxicity and nephrotoxicity. In particular, the nephrotoxicity mechanism of high-dose vancomycin hydrochloride is that vancomycin hydrochloride accumulates in proximal renal tubular cells, causing cell necrosis, which will greatly affect the health of patients. Long-term or high-dose use of other antibiotics will also have similar problems, affecting the health of patients.

[0063] The inventors have thought that the above problems can be further solved by combining carbon nanoparticles with antibiotics. Specifically, the surface of carbon nanoparticles has a certain degree of roughness. This micro-nano-sized surface structure can provide more cell attachment points and has a high specific surface area. At the same time, the high specific surface area helps to transfer nutrients and provide a good microenvironment for cell growth and proliferation. Therefore, in this embodiment, by combining carbon nanoparticles (such as graphene oxide) with antibiotics (such as vancomycin hydrochloride), it is helpful to slow down the damage of antibiotics to cells.

[0064] More specifically, taking vancomycin hydrochloride as an antibiotic and graphene oxide as a carbon nanoparticle, vancomycin hydrochloride will interact with the phospholipid molecules on the cell membrane, causing changes in cell membrane stability and permeability, thereby affecting the normal function of the cells. At the same time, the use of vancomycin hydrochloride may increase the level of reactive oxygen species (ROS) in the cells and induce the production of inflammatory factors (such as the NF-КB pathway), causing damage to the cell structure and function. The combination of graphene oxide and vancomycin hydrochloride can slow down the damage of vancomycin hydrochloride to cells, because the surface of graphene oxide has a certain degree of roughness. This micro-nano-sized surface structure can provide more cell attachment points, and the high specific surface area helps to transfer nutrients, providing a good microenvironment for cell growth and proliferation.

[0065] The antibacterial coating material provided by the present invention can regulate the degradation rate by adjusting the different mass proportions of the materials to meet the different needs of the clinical environment. It can also use the shape memory effect of polylactic acid and polycaprolactone to regulate the release rate of antibacterial particles, which is beneficial to patient recovery.

[0066] Exemplarily, when the mass ratio of polylactic acid (PLA) and polycaprolactone (PCL) PLA / PCL is equal to 50:50, the degradation rate of the antibacterial coating material is the fastest, the nanofibers of the antibacterial coating material can be hydrolyzed faster, and the drug (i.e., antibacterial particles) in the antibacterial coating material has more opportunities to contact water, thereby promoting faster release of the drug. When the mass ratio of polylactic acid (PLA) and polycaprolactone (PCL) is not 50:50, the degradation rate of the antibacterial coating material will slow down, the hydrolysis rate will slow down accordingly, the drug (i.e., antibacterial particles) will have fewer opportunities to contact water, and the rate of drug release will decrease. In addition, the degree to which the degradation rate of the antibacterial coating material slows down is also affected by the proportion of polylactic acid and polycaprolactone. When the proportion of polycaprolactone is larger, the degree to which the degradation rate of the antibacterial coating material slows down is greater; in contrast, when the proportion of polylactic acid is larger, the degree to which the degradation rate of the antibacterial coating material slows down is smaller.

[0067] Furthermore, the shape memory effect can also help the antibacterial coating material to change shape at a specific temperature, preventing secondary damage to the trachea when placed in the patient. The antibacterial coating material of the present invention can also provide cell active sites, which is conducive to cell adhesion and proliferation, and has good biocompatibility.

[0068] The antibacterial coating material of the present invention, through a specific combination of polylactic acid, polycaprolactone, carbon nanoparticles and antibacterial particles, can not only ensure that the antibacterial coating material has excellent biocompatibility, degradability and antibacterial efficacy, but also can achieve regulation of the release rate of the antibacterial particles through the shape memory effect.

[0069] As a blending system, polylactic acid and polycaprolactone have poor interaction between components and loose bonding at the interface, which is not conducive to practical application. However, after the carbon nanoparticles are doped in the present invention, the adjacent sheets are easily associated, improving their mechanical interaction, thereby significantly enhancing the physical properties of the overall material. At the same time, the addition of carbon nanoparticles can promote the crystallization of the polymer, play the role of a nucleating agent, and improve the crystallization performance of the overall antibacterial coating material. The improvement of the crystallization performance plays the role of grain strengthening, thereby improving the mechanical properties of the material.

[0070] Furthermore, during actual clinical use, heavy metals such as silver and gold will be deposited in the human body, affecting human health. The present invention combines carbon nanoparticles with antibacterial metal particles through hydrogen bonds and interaction forces such as van der Waals forces, and has a stable structure. The carbon nanoparticles are combined with nanofibers by embedding and interaction forces, and the metal particles are not easy to separate from the coating, thereby preventing the deposition of heavy metal particles.

[0071] In addition, although antibiotics have good antibacterial effects, they can also cause damage to cells. By combining carbon nanoparticles with antibiotics, not only can the damage of antibiotics to cells be reduced, but carbon nanoparticles can also provide cell active sites to promote cell adhesion and proliferation.

[0072] Furthermore, in the above-mentioned embodiments, the tensile strength of the antibacterial coating material is in the range of 0.95 to 1.5 MPa. At this time, when in use, the antibacterial coating material can better overcome swallowing and other actions in the human body, preventing damage to the antibacterial coating material and affecting the patient's recovery. The 60-day degradation residual mass of the antibacterial coating material is in the range of 65 to 85%. At this time, the antibacterial coating material will not degrade too quickly and fall off the tracheal stent, and can ensure the effective release of the antibacterial particles, so that the antibacterial particles will not be released too slowly and affect the patient's recovery.

[0073] In a second aspect, an embodiment of the present invention further discloses a tracheal stent, the surface of which is coated with the antibacterial coating material described in any of the aforementioned embodiments.

[0074] By adopting the above technical scheme, the tracheal stent provided by the present invention can achieve regulation of the release rate of the antibacterial particles through the mutual cooperation of the polylactic acid, polycaprolactone and antibacterial particles of the surface antibacterial coating material, and through the shape memory effect of the polylactic acid and polycaprolactone, and can also ensure that the antibacterial coating material has excellent biocompatibility, degradability and antibacterial efficacy.

[0075] In a third aspect, an embodiment of the present invention further discloses a method for preparing an antibacterial coating material, which is used to prepare the antibacterial coating material described in any of the above embodiments, and specifically comprises the following steps:

[0076] Solution preparation: polylactic acid, polycaprolactone, carbon nanoparticles and antibacterial particles are added into an organic solvent and ultrasonically stirred to obtain a mixed solution.

[0077] Electrospinning: The instruments used include a selected container, a propulsion pump and an electrospinning apparatus, and the electrospinning apparatus includes a roller receiver; the mixed solution is placed in the selected container, and the selected container is placed in the propulsion pump, and the propulsion pump propels the mixed solution in the selected container toward the roller receiver; high voltage is applied to the selected container and the roller receiver to form a high voltage electric field, and the high voltage electric field is used to stretch the mixed solution to form a fiber film on the roller receiver.

[0078] Drying: The fiber membrane is dried to obtain an antibacterial coating material.

[0079] By adopting the above technical scheme, the method for preparing antibacterial coating materials can prepare antibacterial coating materials with excellent biocompatibility, degradability and antibacterial efficacy through electrospinning, and can also regulate the release rate of antibacterial particles through shape memory effect.

[0080] In the prior art, 3D printing technology is usually used to prepare tracheal stents. However, this method is limited by the printing equipment and cannot achieve fine structures at the nanoscale. At the same time, it takes a long time to print stents with complex structures. In the present invention, an electrospinning method is used to prepare the antibacterial coating material of the tracheal stent. The electrospinning equipment is usually low-cost and easy to operate. The fiber structure prepared by it is very suitable for simulating natural extracellular matrix, promoting cell attachment and proliferation, and by adding functional nanoparticles, a fiber membrane with antibacterial, cell growth-promoting or specific biological activity can be prepared to increase the functional energy absorption of the stent.

[0081] Furthermore, carbon nanoparticles (such as graphene oxide) are usually difficult to combine with antibacterial particles, and the drug loading rate is low. In the solution preparation step of the present invention, the combination of antibacterial particles and carbon nanoparticles (such as graphene oxide) is increased by using a stirring and oscillating method (i.e., ultrasonic stirring), thereby increasing the drug loading rate. In addition, the tensile strength of a simple polylactic acid / polycaprolactone fiber membrane is low. By adding carbon nanoparticles (such as graphene oxide), the Young's modulus and tensile strength of the fiber membrane can be increased, which is beneficial to ensuring the quality of the antibacterial coating material.

[0082] In the solution preparation step: the ratio of the mass ratio of polylactic acid to polycaprolactone is in the range of 0.1 to 16. More specifically, the mass ratio of polylactic acid to polycaprolactone can be selected from one of the following: 94:6, 83:17, 76:24, 63:37, 55:45, 32:68, 14:86, 90:10, 70:30, 50:50, 30:70, 10:90. Within the above mass ratio range, the full dissolution of polylactic acid and polycaprolactone in the organic solvent can be ensured to obtain a mixed solution with a suitable concentration. Among them, the concentration refers to the overall concentration of polylactic acid and polycaprolactone in the mixed solution. If the concentration is too low, a fiber membrane of antibacterial material with uniform distribution of thickness cannot be formed during the electrospinning process. If the concentration is too high, droplets are easily formed during electrospinning and cannot be stretched into fibers.

[0083] Preferably, the mass ratio of polylactic acid to polycaprolactone is 50:50. In the antibacterial coating material prepared at this time, in terms of structural morphology, the fiber morphology bead string structure is reduced, and the reduction of the bead string structure makes the nanofiber more uniform. In the uniform fiber, the stress distribution is correspondingly more uniform, and it is not easy to form stress concentration at the beads. Therefore, during the use of the antibacterial coating material after being placed in the human body, even if it is repeatedly stressed with the movement of the human body, the antibacterial coating material is not easy to accumulate damage, and the performance of the material will not decrease. In terms of the hydrophilicity of the material, when the mass ratio of polylactic acid to polycaprolactone is 50:50, the swelling rate of the prepared antibacterial coating material is the largest, the water absorption rate is relatively stable, and it can increase the chance of the drug (i.e., the antibacterial particles) to contact with water, accelerate the release of the drug, and facilitate faster recovery of the patient.

[0084] Furthermore, in the solution preparation step, the organic solvent is selected from at least one of the following: chloroform, dimethylformamide, dichloromethane, acetone, tetrahydrofuran. Since polylactic acid and polycaprolactone are polar substances, polar solvents are required for dissolution.

[0085] Among them, in the mixed solution obtained in the solution preparation step, by mass, polylactic acid and polycaprolactone account for 9-15% of the mixed solution, carbon nanoparticles account for 0.1-1% of the mixed solution, antibacterial particles account for 0.05-7% of the mixed solution, and the remainder is organic solvent.

[0086] Among them, polylactic acid and polycaprolactone account for 9-15% of the mixed solution. Within this range, the content of polylactic acid and polycaprolactone can be kept from being too little to cause the electrospinning preparation process to become an electrospray form and fail to form fibers, and the excessive amount of polylactic acid and polycaprolactone can be prevented from having a negative impact on the fluidity and spinnability of the spinning solution, and avoid the situation where the solution viscosity is too high and the solution may not be able to form a stable Taylor cone during the spraying process, resulting in spray failure. Among them, Taylor Cone refers to a specific cone structure formed during the electrospray ionization (ESI) process. It is the initial form of the liquid under the action of a strong electric field, sprayed through a nozzle and finally forming an ionized spray. The principle of Taylor Cone is based on the Taylor Instability phenomenon. When the charge force on the liquid in the electric field exceeds its surface tension, the stability of the liquid surface is destroyed, thereby forming a cone structure with a gradually sharp tip. Preferably, polylactic acid and polycaprolactone together account for 12% of the mixed solution. At this time, the solution viscosity is appropriate, which is more conducive to ensuring that electrospinning can successfully form fibers.

[0087] The carbon nanoparticles account for 0.1-1% of the mixed solution, which can ensure that the content of carbon nanoparticles in the prepared antibacterial coating material is within an appropriate range (for example, within the range of 1-25%), and the carbon nanoparticles can also reduce the viscosity of polymers such as polylactic acid and polycaprolactone during mixing and fusion, and can refine the fiber diameter when forming fibers by electrospinning. In combination with polylactic acid and polycaprolactone, the Young's modulus and tensile strength of the fibers can be further improved; the carbon nanoparticles can also promote the penetration of water molecules in the fiber membrane of the antibacterial coating material prepared subsequently, increase the swelling rate and water absorption rate of the fiber membrane, accelerate the degradation of the fiber membrane, and make the degradation rate of the fiber membrane moderate, so that the degradation rate of the fiber membrane is not too fast to cause the antibacterial coating material to fall off the tracheal stent, and the degradation rate is not too slow to affect the release of the drug; the glass transition temperature of the fiber membrane can also be reduced, the shape memory thermal activation is accelerated, and the shape recovery speed and efficiency are improved.

[0088] The antibacterial particles account for 0.05-7% of the mixed solution, which can ensure that the antibacterial particles in the subsequently prepared antibacterial coating material are within an appropriate range (for example, 1-15%) by mass, which can not only play a good antibacterial effect, but also avoid excessive antibacterial particle content causing damage to patients.

[0089] Further, in the electrospinning step, the container is selected as a syringe. Specifically, the mixed solution obtained in the solution preparation step is poured into the syringe and a needle is installed. The syringe is placed in a propulsion pump, and the propulsion pump is at a certain position away from the roller receiver of the electrospinning instrument. Specifically, the distance between the propulsion pump and the roller receiver is in the range of 10 to 20 cm. The propulsion pump propels the mixed solution in the syringe in the direction of the roller receiver at a speed in the range of 1 to 3 ml / h. The tin foil received is installed on the roller receiver, and the needle of the syringe and the roller receiver are respectively connected to the high-voltage wire and the ground wire. A high voltage is applied to the needle of the syringe and the roller receiver through the high-voltage wire and the ground wire to form a high-voltage battery, and the mixed solution is stretched by the high-voltage electric field to form a fiber membrane on the tin foil. Among them, the high voltage of the high-voltage electric field is in the range of 5 to 30 kV, the rotation speed of the roller receiver is in the range of 150 to 250 rpm, and the roller receiver receives the fiber membrane while rotating.

[0090] In the process of stretching the mixed solution into a fiber membrane by electrospinning, the solvent in the mixed solution evaporates, and the antibacterial coating material is finally obtained.

[0091] Furthermore, in the drying step, the fiber membrane formed in the electrospinning step is dried within a time range of 24 to 48 hours and a temperature range of 30 to 38° C. to obtain a biodegradable antibacterial coating material.

[0092] Specifically, according to the viscosity of the polymer solution, different molecular weights have different viscosities, and different viscosities have different surface tensions. The electrospinning technology uses the breakdown effect of high-voltage electrostatic fields on polymer solutions to prepare nanofibers. High-voltage static electricity needs to break through the surface tension of the solution to stretch and solidify the solution, forming a jet stream through the needle, and finally forming a fiber film on the receiving plate. If the voltage is small, it cannot form a filament, and if the voltage is large, the fiber diameter is too small and the mechanical properties are poor. Setting the high voltage of the high-voltage electric field in the range of 5 to 30 kV is conducive to forming a fiber film with a suitable fiber diameter and good mechanical properties.

[0093] The distance between the propulsion pump and the drum receiver is within the range of 10 to 20 cm, which can avoid uneven electrospinning membranes caused by being too close, and prevent the electrospinning membranes from being too sparse or even unable to be spun due to being too far away.

[0094] The speed of the propulsion pump matches the voltage of the high-voltage electric field of electrospinning. Both need to be regulated to make the needle droplet form a cone and achieve the best spinning effect. The speed of the propulsion pump is set in the range of 1 to 3 ml / h.

[0095] The speed of the drum receiver. Generally speaking, the faster the drum speed, the greater the stretching degree and the thinner the fiber diameter. However, the unevenness of fiber stretching increases, which easily leads to irregular shape and fiber breakage. If the drum speed is too low, it may cause problems such as increased fiber diameter and distorted shape. Therefore, the speed of the drum receiver is in the range of 150-250rpm.

[0096] If the drying temperature is too high, the fiber will melt; if it is too low, the residual organic solvent cannot be removed; if the drying time is too short, the residual organic solvent cannot be removed; if it is too long, the fiber film will become more brittle and affect the mechanical properties. Therefore, the temperature of the drying step is in the range of 30-38°C and the time is in the range of 24-48 hours.

[0097] The present invention selects the above-mentioned specific parameter range to prepare the antibacterial coating material by the electrospinning method, which can ensure that the antibacterial coating material has good mechanical properties while loading more antibacterial particles, promotes cell growth and has an antibacterial effect.

[0098] In the present invention, the antibacterial coating material is subjected to microscopic morphology observation, mechanical property detection, in vitro drug release performance detection, antibacterial property detection and cell viability detection, and the detection methods used are as follows:

[0099] For microscopic morphology observation (surface morphology observation), a field emission scanning electron microscope (Quanta FEG 450) was used to observe the microscopic morphology of the sample. Before starting the observation, the sample needed to be sprayed with gold to make it conductive. More specific steps are as follows: The microscopic morphology on the fiber membrane was characterized using a Quanta FEG 450 scanning electron microscope (SEM) from FEI. The fiber membrane was glued to the sample stage with conductive tape and sprayed with gold using a vacuum coating machine to increase the conductivity of the sample. When taking SEM images, the working distance (WD) was set to 14.0nm, the acceleration voltage (Hv) was set to 5.0kV, and the Spot was set to 3.0. Different magnifications were selected to observe the microscopic morphology of the fiber membrane on the sample stage. Representative pictures were selected and the fiber diameter was measured using the software Image J.

[0100] For mechanical property testing (tensile test), a universal material testing machine (Zwick, 2.5kN) was used to measure the tensile strength and elongation at break of the sample, with a tensile speed of 10mm / min. The more specific steps are as follows: The Z2.5TH universal material testing machine of Zwick was used for tensile property testing. First, the sample was cut into 6x2cm 2 Rectangular, the instrument's fixtures fix the upper and lower ends of the sample. During the test, the instrument measures the mechanical properties of the sample at a speed of 10mm / min and a clamping distance of 30mm, and each sample is measured in 2 groups.

[0101] For degradation performance testing (degradation rate test), cut the fiber membrane into 2x2cm 2 square, with pre-measured mass W o . Place it in a 10mL centrifuge tube and add 5mL PBS buffer. Perform the experiment at 37.0±0.1℃ and 100rpm. Take out the sample and replace the liquid once every 2 days. Rinse it with deionized water 3 times and blow dry it at 37.0±0.1℃. Calculate the average residual mass (%) according to the following formula: Residual mass ratio (%) = W f / W o × 100%, where W o is the initial mass of the fiber membrane, in grams (g); W f is the final mass of the fiber membrane degraded at each time period, in grams (g).

[0102] For the in vitro drug release performance test (drug release test), this experiment uses PBS as a sustained release medium, and a PBS solution with a pH value of 7.4 is used to simulate the normal human body fluid environment. Exemplarily, the VAN@GO powder and VAN@GO composite fiber membrane prepared from vancomycin hydrochloride, graphene oxide, polylactic acid and polycaprolactone are used as examples to illustrate more specific steps. The VAN@GO powder and VAN@GO composite fiber membrane are placed in a PBS solution with a pH value of 7.4 for sustained release, and 3 parallel experimental groups are performed for each sample. For the powder test, 5 mg of the complex was weighed into a dialysis bag (molecular weight cutoff MWCO is in the range of 8000 to 14000), immersed in 20 mL of PBS solution, and sustained release was performed in a constant temperature shaking incubator at 37°C with an oscillation frequency of 100 rpm. In the test of the fiber membrane, the fiber membrane was cut into 2x2 cm 2 The size sample was then soaked in 3mL of PBS buffer and then placed in a 37°C constant temperature shaking incubator for sustained release. Samples were taken at pre-set time points (1h, 2h, 3h, 4h, 5h, 10h, 24h, 36h), 2mL of solution was taken from the sustained release sample and placed in a PBS solution of the same content at the same time, and then the release amount of VAN (vancomycin hydrochloride) was measured by UV-Vis. The cumulative drug release amount was calculated as follows: CR (%) = M r / M b ×100%, where M r is the amount of drug released, M b is the total drug loading capacity of the carrier.

[0103] For antimicrobial performance testing (antimicrobial testing), there are three steps:

[0104] (1) Culture of bacterial strains: Single clones of Staphylococcus aureus and Escherichia coli were selected and placed in 10 mL of liquid Luria-Bertani medium, and then cultured overnight in a 37°C constant temperature shaker. The concentration of the enriched bacterial solution was measured using an ultraviolet spectrophotometer and then diluted in a gradient to prepare 10 6 CFU·mL -1 The bacterial suspension is ready for use.

[0105] (2) Sample sterilization: Cut the fiber membrane into small discs with a diameter of 6 mm, and then put them into the autoclave for ethylene oxide sterilization for 14 hours. After complete disinfection, turn on the ventilation device to exhaust the ethylene oxide gas in the sterilization chamber, and take out the sterilized samples for storage.

[0106] (3) Inhibition ring method: Take 100 μL of a 10 6 CFU·mL -1 The bacterial suspension was added to the LB solid culture medium plate, and the VAN control group and the four experimental groups were gently attached to the surface of the plate after being evenly coated. After 24 hours of incubation, the images were observed and collected. The experimental bacteria were Staphylococcus aureus and Streptococcus pneumoniae.

[0107] For cell viability detection, the following steps are performed:

[0108] (1) Culture of airway epithelial cells: Rat tracheal epithelial cells (CP-R004, Pricella), take out the T25 cell culture flask, disinfect the flask with 75% alcohol, remove the sealing film, and place it in a cell culture incubator at 37°C, 5% CO2, and saturated humidity for 3-4 hours to stabilize the cell state. Then wash it three times with PBS buffer, add 1 mL of 0.25% trypsin digestion solution to the T25 culture flask, gently rotate the culture flask until the digestion solution covers the entire bottom of the culture flask, and let it stand in the cell culture incubator for 3 minutes. Observe under an inverted microscope, and after the cells shrink and become round, add 3 mL of complete culture medium (10% fetal bovine serum (BI), 100 IU / mL penicillin and 100 μg / mL streptomycin (Seville), HG-DMEM (Seville)) to terminate digestion. Subculture according to a 1:2 ratio, and replace the complete culture medium every 3 days.

[0109] (2) Sample processing: sterilize the fiber membrane. Cut the fiber membrane into 1x1cm 2 The cut samples are then placed in a clean and sterile culture dish, followed by ultraviolet sterilization treatment on a clean bench for 24 hours.

[0110] (3) After the sample is processed, the cell proliferation capacity can be measured:

[0111] Cell proliferation ability determination: In order to evaluate the proliferation ability of cells on biomaterials, Live / Dead cytotoxicity kit was used for cell staining. The cultured airway epithelial cells were implanted into four samples, and after 1 week of culture in complete medium, Live / Dead staining was performed according to the reagent instructions, and the samples were placed on a laser confocal microscope (Olympus, Japan) for image analysis.

[0112] Specific embodiments are described below.

[0113] (1) Embodiment 1:

[0114] This embodiment provides an antibacterial coating material. The material of the base of the antibacterial coating material is polylactic acid, polycaprolactone and graphene oxide. The antibacterial particles are vancomycin hydrochloride, and the mass percentage of vancomycin hydrochloride is 5%.

[0115] The antibacterial coating material of this embodiment is prepared by the following method:

[0116] 15 mg of vancomycin hydrochloride was dispersed in water to form a solution with a concentration of 1 mg / mL, 60 mg of graphene oxide was added to the vancomycin hydrochloride solution, the mixture was ultrasonicated for 1 hour and stirred at 25°C for 24 hours, then placed in a centrifuge and centrifuged at 12000 rpm for 30 minutes to remove the vancomycin hydrochloride not loaded on the graphene oxide. The sediment was freeze-dried to obtain vancomycin hydrochloride@graphene oxide composite powder.

[0117] Then, 20 mg of vancomycin hydrochloride @ graphene oxide powder was weighed and added to 1 mL of dimethylformamide. The solution was ultrasonicated for 2 hours and stirred for half an hour, and the cycle was repeated 3 times to obtain a uniformly dispersed GO solution (i.e., graphene oxide solution). 500 mg of polylactic acid and 500 mg of polycaprolactone were weighed and added to a mixed solution of 4 mL of chloroform and 1 mL of dimethylformamide and stirred until the polymer was completely dissolved. The GO solution (i.e., graphene oxide solution) was added to the above mixed solution and stirred for 24 hours to obtain a uniform and stable mixed solution.

[0118] The mixed solution prepared from the mixed solution prepared above is added to the syringe, the needle is selected as 21G and installed at the end of the needle tube, and the syringe is placed in the electrospinning instrument at a position 14cm away from the receiver. The receiving tin foil is installed on the receiver. During the spinning process, the instrument voltage is set to 15kV, the humidity is 25%, the propulsion pump speed is set to 2mL / h, and the speed of the drum receiver is 220rpm. After the electrospinning is completed, the fiber membrane attached to the aluminum foil is placed in a fume hood together with the aluminum foil and dried at room temperature for 36h, and then the fiber membrane is removed from the aluminum foil to obtain an antibacterial coating material.

[0119] In the antibacterial coating material prepared by the above method, by mass, graphene oxide accounts for 16% of the antibacterial coating material, vancomycin hydrochloride accounts for 4% of the antibacterial coating material, and the remainder is polylactic acid and polycaprolactone.

[0120] The macroscopic morphology of the antibacterial coating material of Example 1 is as follows: Figure 1 As shown, from Figure 1 It can be seen that the fiber membrane can be rolled into a cylindrical shape, and the size of the rolled cylindrical shape can be about 6 cm. The microscopic morphology of the antibacterial coating material of Example 1 is as follows Figure 2 As shown, from Figure 2 It can be seen that the fiber thickness is evenly distributed, and there is basically no bead-like defect structure.

[0121] The mechanical properties of the antibacterial coating material prepared in this embodiment were tested, and the stress-strain curve obtained by the test was as shown in FIG. Figure 3 As shown, from Figure 3 It can be seen that the tensile strength of the biodegradable antibacterial coating material prepared in this embodiment is 1.43 MPa.

[0122] The degradation performance of the antibacterial coating material prepared in this embodiment was tested, and the degradation residual mass curve obtained by the test was as shown in FIG. Figure 4 As shown, from Figure 4 It can be seen that the remaining mass of the biodegradable antibacterial coating material prepared in this embodiment is 69.8% after 72 days.

[0123] The antibacterial coating material prepared in this example was subjected to an in vitro drug release test, wherein the in vitro drug release curve obtained by the test is shown in FIG. Figure 5 As shown, from Figure 5 It can be seen that the vancomycin hydrochloride in the biodegradable antibacterial coating material prepared in this example was released by 2.3% in 2 hours, and then the release rate gradually increased. After 12 hours, the release rate began to slow down, and finally it was completely released after 96 hours.

[0124] The antibacterial performance of the antibacterial coating material prepared in this embodiment was tested, and the antibacterial circle of Staphylococcus aureus was as shown in the figure. Figure 6 As shown, Figure 6 The antibacterial coating material (i.e., VAN@GO fiber membrane) and its antibacterial ring are shown. Figure 6 In the part circled by the black dotted line, the middle white part is a part of the VAN@GO fiber membrane, and the large circle on the outside is the antibacterial circle with a diameter of 19.2 mm. It can be seen that the antibacterial coating material prepared in this embodiment has good antibacterial ability.

[0125] The cell viability test of the antibacterial coating material prepared in this example was performed, and the test results are as follows: Fig. 7A As shown, in Fig. 7AThe overall cell viability graph for rat epithelial cells is shown in Figure , which is an image obtained after staining live and dead cells. Figure 7B Only shown in Fig. 7A The fraction of live cells in the total cell activity map is Figure 7C Only shown in Fig. 7A The fraction of dead cells in a plot of total cell viability. Figure 7B and Figure 7C After that you can get Fig. 7A It can be seen that most of them are living cells, and the obtained antibacterial coating material shows good cell survival rate within 7 days.

[0126] (2) Embodiment 2:

[0127] This embodiment provides an antibacterial coating material. The material of the base of the antibacterial coating material is polylactic acid, polycaprolactone and graphene oxide. The antibacterial particles are vancomycin hydrochloride, and the mass percentage of vancomycin hydrochloride is 5%.

[0128] The antibacterial coating material of this embodiment is prepared by the following method:

[0129] 15 mg of vancomycin hydrochloride was dispersed in water to form a solution with a concentration of 1 mg / mL, 60 mg of graphene oxide was added to the vancomycin hydrochloride solution, the mixture was ultrasonicated for 1 hour and stirred at 25°C for 24 hours, then placed in a centrifuge and centrifuged at 12000 rpm for 30 minutes to remove the vancomycin hydrochloride not loaded on the graphene oxide. The sediment was freeze-dried to obtain vancomycin hydrochloride@graphene oxide composite powder.

[0130] Then, 20 mg of vancomycin hydrochloride @ graphene oxide powder was weighed and added to 1 mL of dimethylformamide. The solution was ultrasonicated for 2 hours and stirred for half an hour, and the cycle was repeated 3 times to obtain a uniformly dispersed GO solution (i.e., graphene oxide solution). 700 mg of polylactic acid and 300 mg of polycaprolactone were weighed and added to a mixed solution of 4 mL of chloroform and 1 mL of dimethylformamide and stirred until the polymer was completely dissolved. The GO solution (i.e., graphene oxide solution) was added to the above mixed solution and stirred for 24 hours to obtain a uniform and stable mixed solution.

[0131] The mixed solution prepared from the mixed solution prepared above is added to the syringe, the needle is selected as 21G and installed at the end of the needle tube, and the syringe is placed in the electrospinning instrument at a position 14cm away from the receiver. The receiving tin foil is installed on the receiver. During the spinning process, the instrument voltage is set to 15kV, the humidity is 25%, the propulsion pump speed is set to 2mL / h, and the speed of the drum receiver is 220rpm. After the electrospinning is completed, the fiber membrane attached to the aluminum foil is placed in a fume hood together with the aluminum foil and dried at room temperature for 36h, and then the fiber membrane is removed from the aluminum foil to obtain an antibacterial coating material.

[0132] In the antibacterial coating material prepared by the above method, by mass, graphene oxide accounts for 16% of the antibacterial coating material, vancomycin hydrochloride accounts for 4% of the antibacterial coating material, and the remainder is polylactic acid and polycaprolactone.

[0133] (3) Embodiment 3:

[0134] This embodiment provides an antibacterial coating material. The material of the base of the antibacterial coating material is polylactic acid, polycaprolactone and graphene oxide. The antibacterial particles are vancomycin hydrochloride, and the mass percentage of vancomycin hydrochloride is 5%.

[0135] The antibacterial coating material of this embodiment is prepared by the following method:

[0136] 15 mg of vancomycin hydrochloride was dispersed in water to form a solution with a concentration of 1 mg / mL, 60 mg of graphene oxide was added to the vancomycin hydrochloride solution, the mixture was ultrasonicated for 1 hour and stirred at 25°C for 24 hours, then placed in a centrifuge and centrifuged at 12000 rpm for 30 minutes to remove the vancomycin hydrochloride not loaded on the graphene oxide. The sediment was freeze-dried to obtain vancomycin hydrochloride@graphene oxide composite powder.

[0137] Then, 20 mg of vancomycin hydrochloride @ graphene oxide powder was weighed and added to 1 mL of dimethylformamide. The solution was ultrasonicated for 2 hours and stirred for half an hour, and the cycle was repeated 3 times to obtain a uniformly dispersed GO solution (i.e., graphene oxide solution). 300 mg of polylactic acid and 700 mg of polycaprolactone were weighed and added to a mixed solution of 4 mL of chloroform and 1 mL of dimethylformamide and stirred until the polymer was completely dissolved. The GO solution (i.e., graphene oxide solution) was added to the above mixed solution and stirred for 24 hours to obtain a uniform and stable mixed solution.

[0138] The mixed solution prepared from the mixed solution prepared above is added to the syringe, the needle is selected as 21G and installed at the end of the needle tube, and the syringe is placed in the electrospinning instrument at a position 14cm away from the receiver. The receiving tin foil is installed on the receiver. During the spinning process, the instrument voltage is set to 15kV, the humidity is 25%, the propulsion pump speed is set to 2mL / h, and the speed of the drum receiver is 220rpm. After the electrospinning is completed, the fiber membrane attached to the aluminum foil is placed in a fume hood together with the aluminum foil and dried at room temperature for 36h, and then the fiber membrane is removed from the aluminum foil to obtain an antibacterial coating material.

[0139] In the antibacterial coating material prepared by the above method, by mass, graphene oxide accounts for 16% of the antibacterial coating material, vancomycin hydrochloride accounts for 4% of the antibacterial coating material, and the remainder is polylactic acid and polycaprolactone.

[0140] (4) Embodiment 4:

[0141] This embodiment provides an antibacterial coating material, wherein the material of the matrix is ​​polylactic acid, polycaprolactone and graphene oxide, and the antibacterial particles are silver metal nanoparticles.

[0142] The antibacterial material of this embodiment is prepared by the following method:

[0143] Take 200 mg of graphene oxide and dissolve it in 50 mL of deionized water. Place the beaker in an ultrasonic bath for 1 hour until GO (i.e., graphene oxide) is completely dispersed; 150 mg of silver nitrate is dissolved in 5 mL of deionized water, and 3% ammonia water is dripped into the silver nitrate aqueous solution until the precipitate just disappears, and a silver ammonia solution is prepared for standby use; the dispersed GO dispersion and the silver ammonia solution are stirred and mixed, and placed in a 60°C water bath to react for 40 minutes; then 60 mL of an aqueous solution containing 1.5 g of glucose is added, the water bath is heated to 100°C, and the stirring reaction is continued for 1.5 hours; finally, after the reaction solution is naturally cooled, the product is washed and filtered several times with ethanol and deionized water, and then the precipitate is placed at 70°C and vacuum dried for 27 hours to obtain silver@graphene oxide composite nanoparticles.

[0144] Then weigh 20 mg of silver @ graphene oxide powder and add it to 1 mL of dimethylformamide. Ultrasonicate the solution for 2 hours and stir for half an hour, cycle 3 times, and obtain a uniformly dispersed GO solution (i.e., graphene oxide solution). Weigh 500 mg of polylactic acid and 500 mg of polycaprolactone and add them to a mixed solution of 4 mL of chloroform and 1 mL of dimethylformamide and stir thoroughly until the polymer is completely dissolved. Add the GO solution (i.e., graphene oxide solution) to the above mixed solution and stir for 24 hours to obtain a uniform and stable mixed solution. Among them, the mass ratio of polylactic acid to polycaprolactone is 50:50.

[0145] The mixed solution prepared from the mixed solution prepared above is added to the syringe, the needle is selected as 21G and installed at the end of the needle tube, and the syringe is placed in the electrospinning instrument at a position 15cm away from the receiver. The receiving tin foil is installed on the receiver. During the spinning process, the instrument voltage is set to 15.5kV, the humidity is 30%, the propulsion pump speed is set to 2.2mL / h, and the speed of the drum receiver is 210rpm. After the electrospinning is completed, the fiber membrane attached to the aluminum foil is placed in a fume hood together with the aluminum foil and dried at room temperature for 24h, and then the fiber membrane is removed from the aluminum foil to obtain a biodegradable antibacterial coating material.

[0146] In the antibacterial coating material prepared by the above method, by mass, graphene oxide accounts for 10% of the antibacterial coating material, silver particles account for 10% of the antibacterial coating material, and the remainder is polylactic acid and polycaprolactone.

[0147] A comparative example is described below.

[0148] (1) Comparative Example 1:

[0149] This comparative example provides an antibacterial coating material, the matrix material of the antibacterial coating material is polyvinylidene fluoride (PVDF) and graphene oxide, the antibacterial particles are vancomycin hydrochloride, and the mass percentage of vancomycin hydrochloride is 5%.

[0150] The antibacterial coating material of this comparative example is prepared by the following method:

[0151] 15 mg of vancomycin hydrochloride was dispersed in water to form a solution with a concentration of 1 mg / mL, 60 mg of graphene oxide was added to the vancomycin hydrochloride solution, the mixture was ultrasonicated for 1 hour and stirred at 25°C for 24 hours, then placed in a centrifuge and centrifuged at 12000 rpm for 30 minutes to remove the vancomycin hydrochloride not loaded on the graphene oxide. The sediment was freeze-dried to obtain vancomycin hydrochloride@graphene oxide composite powder.

[0152] Then, 25 mg of vancomycin hydrochloride @ graphene oxide powder was weighed and added to 1 mL of dimethylformamide. The solution was ultrasonicated for 2 hours and stirred for half an hour, and the cycle was repeated 3 times to obtain a uniformly dispersed GO solution (i.e., graphene oxide solution). 1000 mg of polyvinylidene fluoride was weighed and added to a mixed solution of 4 mL of dimethylformamide and 1 mL of acetone and stirred until the polymer was completely dissolved. The GO solution (i.e., graphene oxide solution) was added to the above mixed solution and stirred for 24 hours to obtain a uniform and stable mixed solution.

[0153] The mixed solution prepared from the mixed solution prepared above is added to the syringe, the needle is selected as 18G and installed at the end of the needle tube, and the syringe is placed in the electrospinning instrument at a position 10cm away from the receiver. The receiving tin foil is installed on the receiver. During the spinning process, the instrument voltage is set to 20kV, the humidity is 25%, the propulsion pump speed is set to 1mL / h, and the speed of the drum receiver is 220rpm. After the electrospinning is completed, the fiber membrane attached to the aluminum foil is placed in a fume hood together with the aluminum foil and dried at room temperature for 36h, and then the fiber membrane is removed from the aluminum foil to obtain an antibacterial coating material.

[0154] In the antibacterial coating material prepared by the above method, by mass, graphene oxide accounts for 14% of the antibacterial coating material, vancomycin hydrochloride accounts for 4% of the antibacterial coating material, and the remainder is polyvinylidene fluoride.

[0155] (2) Comparative Example 2:

[0156] This comparative example provides an antibacterial coating material, the substrate of the antibacterial coating material is made of polylactic acid and polycaprolactone, the antibacterial particles are vancomycin hydrochloride, and the mass percentage of vancomycin hydrochloride is 5%. The antibacterial coating material does not contain carbon nanoparticles.

[0157] The antibacterial coating material of this comparative example is prepared by the following method:

[0158] Weigh 20 mg of vancomycin hydrochloride powder and add it to 1 mL of dimethylformamide. Ultrasonicate the solution for 2 hours and stir for half an hour. Repeat this process three times to obtain a uniformly dispersed solution. Weigh 500 mg of polylactic acid and 500 mg of polycaprolactone and add them to a mixed solution of 4 mL of chloroform and 1 mL of dimethylformamide and stir until the polymer is completely dissolved. Add the GO solution to the mixed solution and stir for 24 hours to obtain a uniform and stable mixed solution.

[0159] The mixed solution prepared from the mixed solution prepared above is added to the syringe, the needle is selected as 21G and installed at the end of the needle tube, and the syringe is placed in the electrospinning instrument at a position 14cm away from the receiver. The receiving tin foil is installed on the receiver. During the spinning process, the instrument voltage is set to 15kV, the humidity is 25%, the propulsion pump speed is set to 2mL / h, and the speed of the drum receiver is 220rpm. After the electrospinning is completed, the fiber membrane attached to the aluminum foil is placed in a fume hood together with the aluminum foil and dried at room temperature for 36h, and then the fiber membrane is removed from the aluminum foil to obtain an antibacterial coating material.

[0160] In the antibacterial coating material prepared by the above method, vancomycin hydrochloride accounts for 4% of the antibacterial coating material by mass, and the remainder is polylactic acid and polycaprolactone.

[0161] The specific test results are introduced below. In terms of microscopic morphology observation (surface morphology observation), the results are shown in Table 1.

[0162] Table 1 Surface morphology

[0163] Smooth surface Bead string defects Example 1 smooth few Example 2 Smoother More Example 3 Not smooth many Example 4 smooth few Comparative Example 1 Smoother More Comparative Example 2 Smoother More

[0164] In terms of mechanical properties testing (tensile test), the results are shown in Table 2.

[0165] Table 2 Tensile test

[0166] Tensile strength(MPa) Example 1 1.43MPa Example 2 1.31MPa Example 3 0.95MPa Example 4 1.36MPa Comparative Example 1 0.92MPa Comparative Example 2 0.55MPa

[0167] In terms of degradation performance testing (degradation rate test), the results are shown in Table 3. Generally, the longest time that the antibacterial coating material of the tracheal stent is placed in the human body is 60 days, so the degradation performance for 60 days is tested.

[0168] Table 3 Degradation rate test

[0169] 60-day degradation residual mass (%) Example 1 69.8% Example 2 75.8% Example 3 84.8% Example 4 73.5% Comparative Example 1 87.2% Comparative Example 2 72.3%

[0170] In terms of in vitro drug release performance testing (drug release test), the results are shown in Table 4.

[0171] Table 4 Drug release

[0172]

[0173] In terms of antibacterial performance testing (antibacterial test), the results are shown in Table 5.

[0174] Table 5 Antibacterial test

[0175] Diameter of inhibition zone after 24 hours Example 1 19.2mm Example 2 18.4mm Example 3 17.8mm Example 4 16.5mm Comparative Example 1 16.4mm Comparative Example 2 15.5mm

[0176] In terms of cell viability detection, the results are shown in Table 6, which are the results of cell proliferation ability.

[0177] Table 6 Cell activity

[0178] Dead cell count Viable cell count Example 1 few many Example 2 less More Example 3 less More Example 4 few many Comparative Example 1 less More Comparative Example 2 many few

[0179] Taking the above results into consideration, the antibacterial coating material of Example 1 contains polylactic acid and polycaprolactone, and the mass ratio of polylactic acid to polycaprolactone is 50:50. By mass, graphene oxide accounts for 16% of the antibacterial coating material, and vancomycin hydrochloride accounts for 4% of the antibacterial coating material. In terms of surface morphology, the surface is smooth and has few bead defects; in terms of mechanical property detection (tensile test), the tensile strength is 1.43 MPa, and the tensile strength is high; in terms of degradation performance detection (degradation rate test), the residual mass after 60-day degradation is 69.8%, and the degradation rate is fast; in terms of in vitro drug release performance detection (drug release test), the release amount of the antibiotic drug vancomycin hydrochloride is significantly increased after shape memory; in terms of antibacterial performance detection (antibacterial test), the diameter of the inhibition zone after 24 hours is 19.2 mm, and the antibacterial performance is good; in terms of cell viability detection, the amount of living cells on the antibacterial coating material of Example 1 is large, the amount of dead cells is small, and the cell proliferation ability is strong.

[0180] The antibacterial coating material of Example 2 contains polylactic acid and polycaprolactone, and the mass ratio of polylactic acid to polycaprolactone is 70:30. By mass, graphene oxide accounts for 16% of the antibacterial coating material, and vancomycin hydrochloride accounts for 4% of the antibacterial coating material. In terms of surface morphology, the surface is relatively smooth and has more bead defects; in terms of mechanical property detection (tensile test), the tensile strength is 1.31 MPa, and the tensile strength is high; in terms of degradation performance detection (degradation rate test), the residual mass after 60 days of degradation is 75.8%; in terms of in vitro drug release performance detection (drug release test), the release amount of the antibiotic drug vancomycin hydrochloride is significantly increased after shape memory; in terms of antibacterial performance detection (antibacterial test), the diameter of the inhibition zone after 24 hours is 18.4 mm, and the antibacterial performance is good; in terms of cell viability detection, the amount of live cells on the antibacterial coating material of Example 2 is large, the amount of dead cells is small, and the cell proliferation ability is strong.

[0181] The antibacterial coating material of Example 3 contains polylactic acid and polycaprolactone, and the mass ratio of polylactic acid to polycaprolactone is 30:70. By mass, graphene oxide accounts for 16% of the antibacterial coating material, and vancomycin hydrochloride accounts for 4% of the antibacterial coating material. In terms of surface morphology, the surface is not smooth enough and has many bead defects; in terms of mechanical property detection (tensile test), the tensile strength is 0.95MPa; in terms of degradation performance detection (degradation rate test), the residual mass after 60 days of degradation is 84.8%; in terms of in vitro drug release performance detection (drug release test), the release amount of the antibiotic drug vancomycin hydrochloride is significantly increased after shape memory; in terms of antibacterial performance detection (antibacterial test), the diameter of the inhibition zone after 24 hours is 17.8mm, and the antibacterial performance is good; in terms of cell viability detection, the amount of live cells on the antibacterial coating material of Example 3 is large, the amount of dead cells is small, and the cell proliferation ability is strong.

[0182] The antibacterial coating material of Example 4 contains polylactic acid and polycaprolactone, and the mass ratio of polylactic acid to polycaprolactone is 50:50. By mass, graphene oxide accounts for 10% of the antibacterial coating material, and silver particles account for 10% of the antibacterial coating material. In terms of surface morphology, the surface is smooth and there are few bead defects; in terms of mechanical property detection (tensile test), the tensile strength is 1.36 MPa, and the tensile strength is high; in terms of degradation performance detection (degradation rate test), the residual mass after 60-day degradation is 73.5%, and the degradation rate is relatively fast; in terms of antibacterial performance detection (antibacterial test), the diameter of the inhibition zone after 24 hours is 16.5 mm, and the antibacterial performance is good; in terms of cell viability detection, the amount of live cells on the antibacterial coating material of Example 4 is large, the amount of dead cells is small, and the cell proliferation ability is strong.

[0183] In the comparative example, in the antibacterial coating material of comparative example 1, by mass, graphene oxide accounts for 14% of the antibacterial coating material, vancomycin hydrochloride accounts for 4% of the antibacterial coating material, and the remainder is polyvinylidene fluoride. Since polylactic acid and polycaprolactone are not used, polylactic acid, polycaprolactone, graphene oxide, and vancomycin hydrochloride are not combined. In terms of mechanical property detection (tensile test), the tensile strength is 0.92MPa, which is low and difficult to meet the tensile strength of the antibacterial coating material of the tracheal stent; in terms of in vitro drug release performance detection (drug release test), polyvinylidene fluoride in the antibacterial coating material does not have a shape memory effect, and the drug release rate cannot be regulated by shape memory; in terms of antibacterial performance detection (antibacterial test), the diameter of the antibacterial zone after 24 hours is only 16.4mm, and the antibacterial performance is poor, which is not as good as Examples 1-4.

[0184] In the antibacterial coating material of comparative example 2, vancomycin hydrochloride accounts for 4% of the antibacterial coating material by mass, and the remainder is polylactic acid and polycaprolactone, and carbon nanoparticles are not included. Since carbon nanoparticles are not included, and carbon nanoparticles are not combined with antibiotic drugs, polylactic acid and polycaprolactone, the tensile strength of the antibacterial coating material is only 0.55MPa, which is low in tensile strength and does not meet the tensile strength of the antibacterial coating material of the tracheal stent; the diameter of the inhibition zone after 24 hours is only 15.5mm, and the antibacterial performance is poor; in terms of cell viability detection, the amount of dead cells on the antibacterial coating material of comparative example 2 is large, the amount of live cells is small, and the cell proliferation ability is weak, which is not suitable for the use requirements of the antibacterial coating material of the tracheal stent.

[0185] The present invention dopes carbon nanoparticles and antibacterial particles into polylactic acid / polycaprolactone by an electrostatic spinning method, improves the mechanical properties, hydrophilic properties, biodegradation and biocompatibility of polylactic acid / polycaprolactone, and imparts good antibacterial properties. Polylactic acid and polycaprolactone are high molecular polymers with excellent properties such as non-toxicity, biodegradability and biocompatibility. Their degradation products are H2O and CO2 that can be absorbed by the human body, which can reduce adverse stimulation to cells. At the same time, polylactic acid and polycaprolactone also have shape memory function, and can change shape through thermal response, which can not only facilitate implantation in patients, but also regulate the release rate of antibiotic drugs.

[0186] More specifically, the present invention has a specific shape memory effect brought about by a specific polylactic acid polycaprolactone mass ratio, thereby affecting the drug release rate. In addition, the present invention also combines carbon nanoparticles with antibacterial particles, so that the antibacterial coating material has antibacterial properties, and the tracheal stent coated with the antibacterial coating material of the above embodiments also has antibacterial properties accordingly; due to different treatment conditions, there are requirements for the release of drugs, and the release rate of different drugs can be controlled by the shape memory effect of polylactic acid and polycaprolactone. Further, when the antibacterial particles are antibiotic drugs, the antibiotic drugs may cause damage to cells, and the combination of carbon nanoparticles and antibiotic drugs can slow down the damage of antibiotic drugs to cells. When the antibacterial particles are antibacterial metal particles, the antibacterial metal particles are easy to detach from the nanofiber coating of the antibacterial coating material. If absorbed by cells, it will cause human body reactions such as inflammation, causing secondary damage to patients. Through the combination of antibacterial metal particles and carbon nanoparticles, the antibacterial metal particles can be firmly maintained on the surface of the antibacterial coating material and will not detach from the antibacterial coating material.

[0187] Although the present invention has been illustrated and described with reference to certain preferred embodiments of the present invention, it should be understood by those skilled in the art that the above is a further detailed description of the present invention in conjunction with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Those skilled in the art may make various changes in form and details, including making several simple deductions or substitutions, without departing from the spirit and scope of the present invention.

Claims

1. An antibacterial coating material, characterized in that: The antibacterial coating material comprises a substrate and antibacterial particles, wherein the antibacterial particles are distributed on the surface of the substrate, the material of the substrate is polylactic acid, polycaprolactone and carbon nanoparticles, and the antibacterial particles are antibacterial metal particles or antibiotic drugs.

2. The antibacterial coating material according to claim 1, characterized in that: By mass, the carbon nanoparticles account for 1-25% of the antibacterial coating material, the antibacterial particles account for 1-15% of the antibacterial coating material, and the remainder is the polylactic acid and the polycaprolactone.

3. The antibacterial coating material according to claim 1, characterized in that: The carbon nanoparticles are selected from at least one of the following: graphene oxide, reduced graphene oxide, graphene, graphene quantum dots, and carbon nanotubes.

4. The antibacterial coating material according to claim 1, characterized in that: The antibacterial metal particles are selected from at least one of the following: silver, copper, gold, zinc oxide, and copper oxide.

5. The antibacterial coating material according to claim 1, characterized in that: The antibiotic drugs are selected from at least one of the following: vancomycin hydrochloride, norvancomycin hydrochloride, polymyxin B, polymyxin E, levofloxacin, amoxicillin, and norfloxacin.

6. A tracheal stent, characterized in that: The surface of the tracheal stent is coated with the antibacterial coating material according to any one of claims 1 to 5.

7. A method for preparing an antibacterial coating material, used for preparing the antibacterial coating material according to any one of claims 1 to 5, characterized in that: include: Solution preparation: adding polylactic acid, polycaprolactone, carbon nanoparticles and antibacterial particles into an organic solvent, performing ultrasonic stirring to obtain a mixed solution; Electrospinning: The apparatus used includes a selected container, a propulsion pump and an electrospinning apparatus, wherein the electrospinning apparatus includes a drum receiver; the mixed solution is placed in the selected container, the selected container is placed in the propulsion pump, and the propulsion pump propels the mixed solution in the selected container toward the drum receiver; Applying high voltage to the selected container and the drum receiver to form a high voltage electric field, wherein the high voltage electric field is used to stretch the mixed solution to form a fiber film on the drum receiver; Drying: Drying the fiber membrane to obtain the antibacterial coating material.

8. The method for preparing the antibacterial coating material according to claim 7, characterized in that: The solution preparation step also includes: the mass ratio of the polylactic acid to the polycaprolactone is in the range of 0.1 to 16.

9. The method for preparing an antibacterial coating material according to claim 7, characterized in that: The solution preparation step also includes: the organic solvent is selected from at least one of the following: chloroform, dimethylformamide, dichloromethane, acetone, and tetrahydrofuran.

10. The method for preparing an antibacterial coating material according to claim 7, characterized in that: The selected container in the electrospinning step is a syringe with a needle on it. The electrospinning step specifically includes the following steps: putting the mixed solution into the syringe, placing the syringe in the propulsion pump, and the distance between the propulsion pump and the roller receiver is in the range of 10 to 20 cm; the propulsion pump propels the mixed solution in the syringe toward the roller receiver at a speed in the range of 1 to 3 ml / h; connecting a high-voltage wire and a ground wire to the needle of the syringe and the roller receiver respectively to apply high voltage to the needle of the syringe and the roller receiver to form the high-voltage electric field, and the high voltage is in the range of 5 to 30 kV; installing tin foil on the roller receiver, setting the rotation speed of the roller receiver in the range of 150 to 250 rpm, so that the roller receiver receives the fiber membrane; in the drying step, drying the fiber membrane in the range of 24 to 48 hours and in the range of 30 to 38°C to obtain the antibacterial coating material.